Given "(1-x^2)y''-2xy'+n(n-1)y=0------->(1)"
Write the differential equation in standard form by dividing both sides of the equation by the coefficient of "y''" : "(1-x^2)"
Now "1-x^2=0 \\implies (1-x)(1+x)=0"
"\\implies x=+1" "or -1"
Thus "x=+1" and "x=-1" are two singular points of "(1)"
Let
"y(x)=\\Sigma ^{\\infin}_{k=0}a_kx^{k+m}""i.e" "y=a_0x^m+a_1x^{m+1}+a_2x^{m+2}+a_3x^{m+3}+...+a_mx^{m+n}----->(2)"
"y'=ma_0x^{m-1}+(m-1)a_1x^{m}+(m+2)a_2x^{m+1}+(m+3)a_3x^{m+2}+...+(m+n)a_mx^{m+n-1}"
"y''=m(m-1)a_0x^{m-2}+(m+1)ma_1x^{m-1}+(m+2)(m-1)a_2x^{m}+(m+3)(m+2)a_3x^{m+1}+...+(m+n)(m+n-1)a_mx^{m+n-2}"
Put the values of "y,y',y''" in "(1)" to get;
"(1-x^2)[m(m-1)a_0x^{m-2}+(m+1)ma_1x^{m-1}+(m+2)(m-1)a_2x^{m}+(m+3)(m+2)a_3x^{m+1}+...]-2x[ma_0x^{m-1}+(m-1)a_1x^{m}+(m+2)a_2x^{m+1}+(m+3)a_3x^{m+2}+...]+n(n-1)[a_0x^m+a_1x^{m+1}+a_2x^{m+2}+a_3x^{m+3}+...+a_mx^{m+n}]=0"
Multiply the terms and simplify to get the Indicial equation
For Indicial equation, the least power of "x" terms are equated to zero
Here, "x^{m-2}" is the least power of "x"
Putting coefficients of "x^{m-2}" equal to zero, we get;
"\\implies m(m-1)=0, a_0 \\ne0"
Thus "m(m-1)=0" is indicial equation"------->(3)"
Now we will find the coefficient "a_0, a_1, a_2, a_3, a_4...." and then find the general solution.
Equating the coefficient of "x^{m-1}=0"
Equating the coefficient of "x^m=0"
Equating the coefficient of "x^{m+1}=0"
Equating the coefficient of "x^{m+2}=0"
"a_4(m+4)(m+3)-a_2[(m+2)(m+1)+2(m+2)-n(n-1)]=0----->(7)"
To find the solution when "m=0"
"a_2=\\frac{-n(n-1)}{2!}a_0"
From "(6)" Put "m=0"
From "(7)" Put "m=0"
Similarly
Since given that "a_1=0" Put values of "a_2, a_3, a_4, a_5" in "(2)" to get
Now Put "m=1"
From "(5)"
From "(6)"
"a_3(4)(3)-a_1[2(1)+2(2)-n(n-1)]=0"Put "a_1=1"
"\\implies a_3=\\frac{6-n(n-1)}{(4)(3)}a_1=-[\\frac{n^2-n-6}{(4)(3)}]a_1=-[\\frac{(n-3)(n+2)}{(4)(3)}]a_1"
From "(7)"
"a_4(5)(4)-a_2[(3)(2)+2(3)-n(n-1)]=0""a_4=\\frac{-a_2}{(5)(4)}[(n-4)(n+3)]"
Putting value of "a_2" we get
Putting the values from "a_0,a_1,a_2,a_3" in "(3)" we get
"y=a_0x^m+a_1x^{m+1}+\\frac{-(n-2)(n+1)}{3!}a_0^{m+2}-\\frac{(n-3)(n+2)}{(4)(3)}a_1x^{m+3}+\\frac{(n-4)(n+3)(n-2)(n+1)}{5!}a_0x^{m+1}"
Put "m=1" and "a=1," we will get odd power terms as
"y=[x+\\frac{-(n-2)(n+1)}{3!}x^2+\\frac{(n-4)(n+3)(n-2)(n+1)}{5!}x^5+...]a_0----->Answer"
Comments
Leave a comment